Propriedades físico-hídricas de solos siltosos sob plantio direto - Broch, Djulia Taís (2016)
Compression is one of the causes of physical degradation in agricultural soils. To measure the soil’s compaction degree, only its density analysis (DS) is insufficient. This is explained on the grounds that its granulometric composition and its organic matter content (OM) are very variable. The soil relative density (RD) is an indicator that allows the compaction degree identification, and, therefore, enables comparison of soil and handlings. The DR is obtained by the ratio between the DS and its maximum density (DSMax). The objective is to verify the influence of silt on physical and hydraulic properties in Neossolos. Were collected samples with preserved and not preserved structure from 18 soil under no-tillage system of Rio Grande do Sul. It was determined the granulometric composition, MO content, DS, DSMax, DR, moisture in the field capacity (FC) and, in permanent wilting point (PWP), the porosity and pore diameter distribution. The results showed that DSMax reduced with the addition of silt and OM and that the clay and the clay+silt had no significant effect. The OM content influenced upon density of soil solids (DSS) and upon the optimum moisture content (OMC). The PDS decreased with silt and OM increasing. PAIN was not influenced by granulometric composition and OM content, and there was noticed differences among the DR determined from the real DSMax and the DR calculated by Dmax estimated by the clay content. The increase in DS reduced the total porosity, macroporosity and the microporosity and increased cryptoporosity. The silt content affects the silty soil physical and hydraulic properties differently than what is perceived in clayey soils.